Active ray-curable composition, method for producing cured film, cured film, and device for producing cured film

By using a (meth)acrylic polymer composition with weight average molecular weight and hydroxyl characteristics, combined with a photopolymerization initiator, the active ray curable composition formed is solved, and the lack of adhesion of curable resins in high temperature and high humidity environments is solved. The problem of poor ejection stability of the inkjet method has achieved improvements in high temperature and high humidity and bending durability, and is suitable for the adhesive of transparent layer of image display devices.

CN119234001APending Publication Date: 2024-12-31KONICA MINOLTA INC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380041733.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-05-25
Filing Date
2023-05-15
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

The conventional curable resin composition has insufficient adhesion in high temperature and high humidity environments and low temperature environments, and has little requirement for bending durability of flexible displays, and has poor ejection stability of inkjet method.

Method used

The active ray curability formed by combining a photopolymerization initiator is formed by using a (meth)acrylic polymer with a weight average molecular weight of 10,000 to 150,000, (meth)acrylic acid ester with a hydroxyl group and a (meth)acrylic acid ester without a hydroxyl group. The composition is formed by inkjet method and is subjected to active ray irradiation at high temperature to improve adhesion and durability.

Benefits of technology

The ejection stability of the inkjet method and the durability of the cured film in a high temperature and high humidity environment are improved, and the durability to bend is ensured, and it is suitable for the adhesive of a transparent layer of the image display device.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119234001A_ABST
    Figure CN119234001A_ABST
Patent Text Reader

Abstract

The present invention provides an active ray-curable composition which can improve ejection stability by an ink jet method, improve durability of a cured film in a high-temperature, high-humidity environment and a low-temperature environment, and improve durability of the cured film with respect to bending. The active ray-curable composition according to the present invention contains the following components (A) to (D), and has a viscosity at 25 DEG C of 10 mPa * s to 200 mPa * s. Component (A): a (meth) acrylic polymer having a weight-average molecular weight of 10000-150000 and a hydroxyl value of 30 mgKOH / g or more Component (B): a (meth) acrylate having a hydroxyl group, Component (C): a (meth) acrylate not having a hydroxyl group, and Component (D): a photopolymerization initiator.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an active ray-curable composition, a method for producing a cured film, a cured film, and an apparatus for producing a cured film. Background Art

[0002] In various image display devices such as liquid crystal display devices and organic electroluminescent (organic EL) display devices, transparent resins are used as adhesives for bonding various components, sealing films, protective films, etc. As such transparent resins, transparent resins obtained by curing curable resin compositions applied by spin coating, die coating, etc. have been used in the past. On the other hand, in order to achieve fine patterning and application to curved parts, curable transparent resins that can be applied by inkjet methods have also been studied.

[0003] For example, Patent Document 1 describes a curable resin composition, which contains (component A) a (meth) acrylic acid oligomer having a molecular weight of 5000 or more, (component B) a (meth) acrylic acid monomer, and (component C) a photoradical polymerization initiator or a thermal radical polymerization initiator, and has a viscosity of 150 mPa·s or less. According to Patent Document 1, the curable resin composition has excellent adhesion between the inorganic substrate and the organic substrate in the image display device when the substrates are bonded together, and can be ejected by an inkjet method.

[0004] In addition, Patent Document 2 describes a curable resin composition, which contains <Component (A)> a (meth)acrylate polymer having a hydroxyl value of 120 mgKOH / g or more and having no (meth)acryloyl group, <Component (B)> a monofunctional (meth)acrylate monomer containing a hydroxyl group, <Component (C)> a monofunctional (meth)acrylate monomer not containing a hydroxyl group, and <Component (D)> a hydrogen abstraction type photopolymerization initiator, and has a viscosity of 10 mPa·s or more at 25°C and 30 mPa·s or less at 60°C. According to Patent Document 2, the curable resin composition can be used to form a cured product arranged between an image display component and a light-transmitting cover component when they are stacked, and can be well ejected by an inkjet method.

[0005] Prior art literature

[0006] Patent Literature

[0007] Patent Document 1: Japanese Patent Application Publication No. 2017-210578

[0008] Patent Document 2: Japanese Patent Application Publication No. 2020-106830 Summary of the invention

[0009] However, when a cured product of a curable resin composition as described in Patent Document 1 is used in an image display device, the adhesiveness maintenance (durability) of the cured film in a high temperature and high humidity environment or a low temperature environment is sometimes insufficient, or the durability of the cured film against bending required when used in a flexible display is sometimes insufficient.

[0010] According to the view of the inventors, by using a material with a hydroxyl group such as patent document 2 to give polarity to the cured film, their durability can be improved. However, if the material with a hydroxyl group is matched to the composition, there is a situation where the ejection stability based on the inkjet method is reduced. On the other hand, it is also considered that if the molecular weight of the polymer component (polymer) is reduced to reduce the viscosity of the composition, the ejection stability will be improved. However, if the molecular weight of the polymer is reduced, the above-mentioned properties required by the cured film will be reduced.

[0011] The present invention has been made in view of the above-mentioned problems, and an object of the present invention is to provide an active ray-curable composition capable of improving the ejection stability by an inkjet method and improving the durability of a cured film in a high-temperature and high-humidity environment and a low-temperature environment, as well as the durability of the cured film against bending, a method for producing a cured film using the active ray-curable composition, a cured film formed from the active ray-curable composition, and an apparatus for producing a cured film using the active ray-curable composition.

[0012] One embodiment of the present invention for achieving the above object relates to the active radiation curable composition of the following [1] to

[10] .

[0013] [1] An active radiation curable composition comprising:

[0014] Component (A): a (meth)acrylic acid polymer having a weight average molecular weight of 10,000 to 150,000 and a hydroxyl value of 30 mgKOH / g or more,

[0015] Component (B): (meth)acrylate having a hydroxyl group,

[0016] Component (C): (meth)acrylate having no hydroxyl group, and

[0017] Component (D): photopolymerization initiator,

[0018] And the viscosity at 25°C is 10 mPa·s to 200 mPa·s.

[0019] [2] The active radiation-curable composition according to [1], wherein the component (C) contains a (meth)acrylate having an alicyclic structure.

[0020] [3] The active radiation-curable composition according to [1] or [2], wherein the component (C) comprises a (meth)acrylate having no alicyclic structure.

[0021] [4] The active radiation-curable composition according to any one of [1] to [3], wherein the component (B) or the component (C) contains a polyfunctional (meth)acrylate.

[0022] [5] The active radiation-curable composition according to any one of [1] to [4], wherein the component (A) is a (meth)acrylic polymer having a weight average molecular weight of 20,000 to 100,000.

[0023] [6] The active radiation-curable composition according to any one of [1] to [5], wherein the component (D) is an intramolecular bond cleavage type photopolymerization initiator.

[0024] [7] The active radiation-curable composition according to any one of [1] to [6], wherein the component (D) is an acylphosphine oxide-based photopolymerization initiator.

[0025] [8] The active radiation curable composition according to any one of [1] to [7], wherein the component (B) is contained in an amount of 25% by mass or more based on the total mass of the active radiation curable composition.

[0026] [9] The active radiation curable composition according to any one of [1] to [8], wherein the component (A) is a (meth)acrylic polymer having a hydroxyl value of 30 mgKOH / g to 120 mgKOH / g.

[0027]

[10] The active radiation curable composition according to any one of [1] to [9], which is an inkjet ink.

[0028]

[11] The active radiation curable composition according to any one of [1] to

[10] , which is used for forming a transparent layer of an image display device.

[0029] Another aspect of the present invention for achieving the above-mentioned object relates to a method for producing a cured film according to the following

[12] .

[0030]

[12] A method for producing a cured film, comprising:

[0031] a step of providing the active radiation curable composition according to any one of [1] to

[11] , and

[0032] A step of irradiating the above-provided active ray-curable composition with active rays.

[0033] Another aspect of the present invention for achieving the above-mentioned object relates to the cured films of the following

[13] and

[14] .

[0034]

[13] A cured film obtained by curing the active radiation-curable composition according to any one of [1] to

[11] .

[0035]

[14] The cured film according to

[13] , which is a transparent layer of an image display device.

[0036] In addition, another embodiment of the present invention for achieving the above-mentioned object relates to the image display device of the following

[15] .

[0037]

[15] An image display device comprising the cured film according to

[13] or

[14] .

[0038] Another aspect of the present invention for achieving the above-mentioned object relates to a cured film production apparatus according to the following

[16] .

[0039]

[16] A device for producing a cured film, comprising:

[0040] an applying unit that applies the active radiation curable composition described in any one of [1] to

[11] to a substrate, and

[0041] The irradiation unit irradiates the above-provided active ray-curable composition with active rays.

[0042] According to the present invention, there can be provided an active ray-curable composition capable of improving the ejection stability by an inkjet method and improving the durability of a cured film in a high-temperature and high-humidity environment and a low-temperature environment, as well as the durability of the cured film against bending, a method for producing a cured film using the active ray-curable composition, a cured film formed from the active ray-curable composition, and an apparatus for producing a cured film using the active ray-curable composition. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] Figure 1A to Figure 1C It is a schematic diagram which shows the exemplary structure of the manufacturing apparatus of the cured film for implementing the manufacturing method of the cured film which concerns on one Embodiment of this invention. DETAILED DESCRIPTION

[0044] 1. Active radiation curable composition

[0045] One embodiment of the present invention relates to an active radiation curable composition, comprising:

[0046] Component (A): a (meth)acrylic acid polymer having a weight average molecular weight of 10,000 to 150,000 and a hydroxyl value of 30 mgKOH / g or more,

[0047] Component (B): (meth)acrylate having a hydroxyl group,

[0048] Component (C): (meth)acrylate having no hydroxyl group, and

[0049] Component (D): photopolymerization initiator,

[0050] And the viscosity at 25°C is 10 mPa·s to 200 mPa·s.

[0051] In the present specification, “(meth)acrylic acid” means acrylic acid or methacrylic acid, “(meth)acryloyl” means acryloyl or methacryloyl, and “(meth)acrylate” means acrylate or methacrylate.

[0052] 1-1. Component (A) (Meth)acrylic acid polymer

[0053] Component (A) is a (meth)acrylic polymer having a weight average molecular weight of 10000 to 150000 and a hydroxyl value of 30 mgKOH / g or more. Component (A) preferably does not have a polymerizable group (more specifically, a (meth)acryloyl group) in the molecule.

[0054] Component (A) imparts adhesiveness to a cured film formed by curing the active radiation curable composition. In particular, by using a polymer having a hydroxyl group as component (A), the cured film can be imparted with appropriate flexibility obtained by using the polymer and good adhesiveness due to the hydroxyl group.

[0055] However, according to the opinions of the present inventors, the molecular weight of the component (A) that can be used to ensure the ejection property based on the inkjet method is limited. When the molecular weight of the component (A) is too large, even if the viscosity of the composition is adjusted to be relatively low by using other components as described in patent document 2, it is easy to produce wire drawing when ejected from the inkjet head, and the ejection speed is difficult to be stable. Therefore, it is difficult to form a fine pattern, so it is impossible to say that the ejection property based on the inkjet method can be satisfactorily ensured. In addition, according to the opinions of the present inventors, if the molecular weight of the component (A) is increased, there is a trend that the adhesion maintenance force (durability of the cured film under the high temperature and humidity environment and the low temperature environment) of the cured film when placed in the high temperature and humidity environment and the low temperature environment is reduced. In order to fully ensure the ejection property based on the inkjet method, in the present embodiment, the weight average molecular weight of the component (A) is made to be less than 150000.

[0056] On the other hand, if the molecular weight of component (A) is reduced, the ejection property based on the inkjet method can be fully ensured, but the adhesion will be extremely reduced. In particular, the adhesion retention when placed in a high temperature and high humidity environment or a low temperature environment (the durability of the cured film in a high temperature and high humidity environment and a low temperature environment), the adhesion retention when applied to a flexible display and bent (the durability of the cured film when bent) and the like are extremely reduced. In order to ensure the retention of these adhesions, in the present embodiment, the weight average molecular weight of component (A) is made to be 10,000 or more.

[0057] From the above viewpoints, the weight average molecular weight (Mw) of the component (A) is preferably 20,000 to 100,000, and more preferably 40,000 to 80,000.

[0058] It should be noted that the weight average molecular weight (Mw) of component (A) in this specification is a weight average molecular weight converted to polystyrene, and is obtained by using HLC-8220GPC (manufactured by Tosoh Corporation), connecting TSG gel SuperMultiporeHZ 4000 (manufactured by Tosoh Corporation), TSG gel SuperMultiporeHZ 3000 (manufactured by Tosoh Corporation) and TSG gelSuperMultiporeHZ 2500 (manufactured by Tosoh Corporation) chromatographic columns, using tetrahydrofuran (THF) as a solvent, setting the column temperature to 40°C, and detecting using an RI (Refractive Index: differential refractive index) detector.

[0059] In order to sufficiently improve the adhesion of the cured film, especially the durability of the cured film in the above-mentioned high temperature and high humidity environment and low temperature environment, the durability of the cured film when bent, etc., in this embodiment, the hydroxyl value of component (A) is set to 30 mgKOH / g or more.

[0060] It should be noted that according to the views of the present inventors, by suppressing the hydroxyl value within an appropriate range, components (A) form hydrogen bonds with each other to simulate polymerization, thereby not easily producing high viscosity of the ink. As a result, it is more difficult to produce wire drawing when ejected from the inkjet head, and the ejection speed can be easily stabilized. In addition, according to the views of the present inventors, if the hydroxyl value of component (A) is increased, there is a tendency for the durability of the cured film in a low temperature environment to decrease. From the viewpoint of improving all these properties, especially the durability of the cured film in a low temperature environment and the stabilization of the ejection speed, the hydroxyl value of component (A) is preferably 30 mgKOH / g or more and less than 180 mgKOH / g, more preferably 30 mgKOH / g or more and less than 120 mgKOH / g, and further preferably 50 mgKOH / g or more and less than 100 mgKOH / g.

[0061] It should be noted that the hydroxyl value of component (A) in this specification is a value measured using a potentiometric titrator (manufactured by Kyoto Electronics Co., Ltd., AT-500N), a glass electrode (manufactured by Kyoto Electronics Co., Ltd., C-173), and an alcohol solution with a KOH concentration of 0.5 mol / L as a titrant. Specifically, the sample is weighed in a 200 mL conical flask, 5 mL of an acetylation reagent is added, and the mixture is reacted in an oil bath at 100°C±5°C for 1 hour. After cooling, 1 mL of water is added, and the mixture is reacted in an oil bath at 100°C±5°C for 10 minutes. After cooling, 5 mL of ethanol is rinsed, and 140 mL of pyridine is added for dilution. The titration is performed using a potentiometric titrator, and the inflection point obtained is taken as the end point. A blank test is also performed using the same method, and the hydroxyl value is calculated by the following formula.

[0062] Hydroxyl value (mgKOH / g) = (V0-V1) × N × 56.11 × f / S + acid value

[0063] S: weight of sample (g)

[0064] V0: The amount of titrant required for the blank test (mL)

[0065] V1: The amount of titrant required for this test (mL)

[0066] N: concentration of titration solution (0.5 mol / L)

[0067] f: Factor of the titrant (1.001)

[0068] It should be noted that the acid value in the above calculation formula is a value measured using a potentiometric titrator (manufactured by Kyoto Electronics Co., Ltd., AT-500N) and a glass electrode (manufactured by Kyoto Electronics Co., Ltd., C-173), using an alcohol solution with a KOH concentration of 0.1 mol / L as a titrant. Specifically, a sample and 80 mL of a mixed solution (toluene: methanol = 4:1) (volume ratio) are added to a 100 mL conical flask to dissolve the sample. Titration is performed using a potentiometric titrator, and the inflection point obtained is taken as the end point. A blank test is also performed using the same method, and the acid value is calculated by the following formula.

[0069] Acid value (mgKOH / g) = (V1-V0) × N × 56.11 × f / S

[0070] S: weight of sample (g)

[0071] V0: The amount of titrant required for the blank test (mL)

[0072] V1: The amount of titrant required for this test (mL)

[0073] N: concentration of titration solution (0.1 mol / L)

[0074] f: Factor of the titrant (1.001)

[0075] From the viewpoint of improving compatibility with component (B) and component (C) to suppress the increase in viscosity of the ink and suppressing stringing when ejected from an inkjet head, component (A) is a (meth)acrylic polymer. Component (A) may be, for example, a copolymer of a (meth)acrylate having a hydroxyl group and a (meth)acrylate not having a hydroxyl group.

[0076] Examples of (meth)acrylates having a hydroxyl group include 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 2-hydroxy-3-chloropropyl (meth)acrylate, 2-hydroxy-3-phenoxypropyl (meth)acrylate, ethylene glycol (meth)acrylate, polyethylene glycol (meth)acrylate, propylene glycol (meth)acrylate, polypropylene glycol (meth)acrylate, and cyclohexyl dimethanol mono(meth)acrylate, etc. These (meth)acrylates having a hydroxyl group may be used alone or in combination of two or more.

[0077] Examples of (meth)acrylates not having a hydroxyl group include (meth)acrylates having a linear or branched alkyl chain having 1 to 18 carbon atoms. Examples of these (meth)acrylates include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, pentyl (meth)acrylate, hexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, octyl (meth)acrylate, isooctyl (meth)acrylate, nonyl (meth)acrylate, isononyl (meth)acrylate, decyl (meth)acrylate, isodecyl (meth)acrylate, lauryl (meth)acrylate, stearyl (meth)acrylate, isostearyl (meth)acrylate, tridecyl (meth)acrylate, and the like. These (meth)acrylates not having a hydroxyl group may be used alone or in combination of two or more.

[0078] In addition, other examples of (meth)acrylates not having a hydroxyl group include (meth)acrylates having an alicyclic structure such as isobornyl (meth)acrylate, dicyclopentenyl (meth)acrylate, dicyclopentenyloxyethyl (meth)acrylate, dicyclopentanyl (meth)acrylate, cyclohexyl (meth)acrylate, trimethylcyclohexyl (meth)acrylate, tetrahydrofurfuryl (meth)acrylate, glycidyl (meth)acrylate, γ-butyrolactone (meth)acrylate, and (meth)acryloylmorpholine, etc. These (meth)acrylates having an alicyclic structure may be used alone or in combination of two or more.

[0079] Among them, component (A) preferably contains a (meth)acrylate having a linear or branched alkyl chain having 1 to 18 carbon atoms as a constituent unit derived from a (meth)acrylate having no hydroxyl group. The proportion of the (meth)acrylate having an alkyl chain is preferably 50% to 100% by mass, more preferably 70% to 100% by mass, and even more preferably 70% to 90% by mass, relative to the total mass of the constituent units derived from the (meth)acrylate having no hydroxyl group.

[0080] The polymerization ratio of these (meth)acrylates is not particularly limited as long as the hydroxyl value of the component (A) is within the above range.

[0081] It should be noted that component (A) may contain constituent units derived from other copolymerizable monomers such as styrene in addition to the constituent units derived from these (meth)acrylates. From the viewpoint of suppressing stringing when ejected from an inkjet head, the ratio of the constituent units derived from the other monomers is preferably 0% to 10% by mass, more preferably 0% to 5% by mass, relative to the total mass of the copolymer.

[0082] The content of component (A) is preferably 1% to 50% by mass, more preferably 1% to 30% by mass, and further preferably 5% to 20% by mass relative to the total mass of the active ray curable composition. If the above content is 1% by mass or more, the adhesion and retention of the cured film are further improved. If the above content is 50% by mass or less, the viscosity of the active ray curable composition can be adjusted to an appropriate range, so that the ejection property from the inkjet head becomes good.

[0083] 1-2. Component (B): (meth)acrylate having a hydroxyl group

[0084] Component (B) is a (meth)acrylate having a hydroxyl group. Component (B) does not include a so-called oligomer.

[0085] Component (B) appropriately improves the strength of the cured film and also imparts adhesiveness via hydroxyl groups.

[0086] Component (B) may be a monofunctional (meth)acrylate having only one (meth)acryloyl group in the molecule, or may be a polyfunctional (meth)acrylate having multiple (meth)acryloyl groups in the molecule. Among them, monofunctional (meth)acrylate is preferred from the viewpoint of improving the flexibility of curability. In addition, in order to improve both flexibility and hardness, monofunctional (meth)acrylate and polyfunctional (meth)acrylate may also be used in combination.

[0087] Moreover, from the viewpoint of suppressing dispersion deviation of the hydroxyl group in the cured film, it is preferable that the component (B) has only one hydroxyl group in the molecule.

[0088] Examples of component (B) include 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 2-hydroxy-3-chloropropyl (meth)acrylate, 2-hydroxy-3-phenoxypropyl (meth)acrylate, ethylene glycol (meth)acrylate, polyethylene glycol (meth)acrylate, propylene glycol (meth)acrylate, polypropylene glycol (meth)acrylate, and cyclohexyl dimethanol mono(meth)acrylate, etc. These (meth)acrylates may be used alone or in combination of two or more.

[0089] The content of component (B) is preferably 1% to 50% by mass, more preferably 25% to 40% by mass, relative to the total mass of the active radiation curable composition. If the content is 1% by mass or more, the viscosity of the ink can be suppressed and the adhesion and retention of the cured film can be further improved.

[0090] 1-3. Component (C): (meth)acrylate having no hydroxyl group

[0091] Component (C) is a (meth)acrylate having no hydroxyl group. Component (C) does not include so-called oligomers.

[0092] Component (C) adjusts the amount of hydroxyl groups in the cured film to an appropriate range, thereby improving the adhesiveness of the cured film and its retention.

[0093] Component (C) may be a monofunctional (meth)acrylate having only one (meth)acryloyl group in the molecule, or may be a polyfunctional (meth)acrylate having multiple (meth)acryloyl groups in the molecule. Among them, monofunctional (meth)acrylate is preferred from the viewpoint of improving the flexibility of curability. In addition, in order to achieve a balance between flexibility and hardness, monofunctional (meth)acrylate and polyfunctional (meth)acrylate may also be used in combination.

[0094] In particular, from the viewpoint of further improving the adhesiveness maintenance of the cured film under a high temperature and high humidity environment, component (C) preferably contains a (meth)acrylate having an alicyclic structure. The (meth)acrylate having an alicyclic structure increases the glass transition temperature (Tg) of the cured film. Thus, the (meth)acrylate having an alicyclic structure reduces the moisture permeability of the cured film, thereby suppressing the reduction in adhesiveness caused by the deterioration of the cured film due to moisture intruding into the cured film.

[0095] Examples of (meth)acrylates having an alicyclic structure include isobornyl (meth)acrylate, dicyclopentenyl (meth)acrylate, dicyclopentenyloxyethyl (meth)acrylate, dicyclopentyl (meth)acrylate, cyclohexyl (meth)acrylate, and trimethylcyclohexyl (meth)acrylate. These (meth)acrylates having an alicyclic structure may be used alone or in combination of two or more.

[0096] The content of the (meth)acrylate having an alicyclic structure is preferably 1% by mass to 50% by mass, more preferably 15% by mass to 40% by mass, based on the total mass of the active radiation-curable composition.

[0097] Moreover, from the viewpoint of further improving the flexibility of a cured film, it is preferable that the component (C) contains a (meth)acrylate which does not have an alicyclic structure. In addition, the component (C) does not contain a so-called oligomer.

[0098] From the viewpoint of more effectively improving the flexibility of the cured film, the (meth)acrylate not having an alicyclic structure is preferably a (meth)acrylate having a linear or branched alkyl chain of 1 to 18 carbon atoms. Examples of these (meth)acrylates include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, pentyl (meth)acrylate, hexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, octyl (meth)acrylate, isooctyl (meth)acrylate, nonyl (meth)acrylate, isononyl (meth)acrylate, decyl (meth)acrylate, isodecyl (meth)acrylate, lauryl (meth)acrylate, stearyl (meth)acrylate, isostearyl (meth)acrylate, tridecyl (meth)acrylate, etc. These (meth)acrylates not having an alicyclic structure may be used alone or in combination of two or more.

[0099] It should be noted that the (meth)acrylate that does not have an alicyclic structure may be a multifunctional (meth)acrylate. The multifunctional (meth)acrylate can appropriately increase the hardness of the cured film. Examples of multifunctional (meth)acrylates include triethylene glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, tripropylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, 1,4-butanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate, neopentyl glycol di(meth)acrylate, dihydroxymethyl-tricyclodecane di(meth)acrylate, PO adduct di(meth)acrylate of bisphenol A, hydroxypivalic acid neopentyl glycol di(meth)acrylate, polytetramethylene glycol di(meth)acrylate, and polytetramethylene glycol di(meth)acrylate. Difunctional (meth)acrylates such as methyl glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, dipropylene glycol di(meth)acrylate and tripropylene glycol di(meth)acrylate, trifunctional (meth)acrylates such as trimethylolpropane tri(meth)acrylate and pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol hexa(meth)acrylate, ditrimethylolpropane tetra(meth)acrylate, glycerol propoxy tri(meth)acrylate and pentaerythritol ethoxy tetra(meth)acrylate, and their modified products. Examples of the above-mentioned modified products include ethylene oxide modified (EO modified) (meth)acrylates with ethylene oxide groups inserted therein and propylene oxide modified (PO modified) (meth)acrylates with propylene oxide inserted therein. The above-mentioned multifunctional (meth)acrylates may be used alone or in combination of two or more.

[0100] From the viewpoint of improving both the adhesiveness maintenance and flexibility of the cured film, the active radiation curable composition preferably contains both (meth)acrylate having an alicyclic structure and (meth)acrylate not having an alicyclic structure as component (C).

[0101] The content of component (C) is preferably 30% to 85% by mass, more preferably 50% to 70% by mass, relative to the total mass of the active radiation curable composition. If the above content is 30% by mass or more, the adhesion and retention of the cured film are further improved. If the above content is 85% by mass or less, the flexibility of the cured film is further improved.

[0102] It should be noted that from the viewpoint of improving the durability of the cured film under high temperature and high humidity environment, component (B) or component (C) preferably contains a multifunctional (meth) acrylate having a polymerizable functional group number of 2 or more. The multifunctional (meth) acrylate may be contained only in either component (B) or component (C), or may be contained in both component (B) and component (C), but is preferably contained at least in component (C). Relative to the gross mass of the active ray curable composition, the content of the multifunctional (meth) acrylate is preferably 0.1% by mass to 5% by mass, more preferably 1% by mass to 3% by mass. By increasing the content of the multifunctional (meth) acrylate, the durability of the cured film under high temperature and high humidity environment can be improved by using a cross-linked structure. By reducing the content of the multifunctional (meth) acrylate, the softness of the cured film caused by the cross-linked structure can be suppressed from being reduced.

[0103] 1-4. Component (D): Photopolymerization initiator

[0104] Component (D) is a photopolymerization initiator.

[0105] Component (D) initiates polymerization of component (B) and component (C) when irradiated with active rays, thereby curing the active ray-curable cured product.

[0106] Component (D) is a radical polymerizable photopolymerization initiator.

[0107] Component (D) may be an intramolecular bond cleavage type free radical polymerization initiator or an intramolecular hydrogen abstraction type free radical polymerization initiator. Among them, compared with the intramolecular hydrogen abstraction type free radical polymerization initiator, the intramolecular bond cleavage type free radical polymerization initiator is less likely to initiate polymerization starting from the hydroxyl groups possessed by components (A) and (B). Therefore, the intramolecular bond cleavage type free radical polymerization initiator is less likely to form a cross-linked structure generated by the above-mentioned polymerization starting from the hydroxyl groups, which can make the cured film softer and more fully improve the durability of the cured film when bent.

[0108] Examples of the intramolecular bond cleavage type radical polymerization initiator include acetophenone-based initiators including diethoxyacetophenone, 2-hydroxy-2-methyl-1-phenylpropane-1-one, benzyl dimethyl ketal, 1-(4-isopropylphenyl)-2-hydroxy-2-methylpropane-1-one, 4-(2-hydroxyethoxy)phenyl-(2-hydroxy-2-propyl)ketone, 1-hydroxycyclohexyl-phenyl ketone, 2-methyl-2-morpholino(4-methylthiophenyl)propane-1-one and 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)-butanone, benzoins including benzoin, benzoin methyl ether and benzoin isopropyl ether, acylphosphine oxide-based initiators including 2,4,6-trimethylbenzoin diphenylphosphine oxide, benzyl and methylphenyl glyoxylates, and the like.

[0109] Among these intramolecular bond cleavage type radical polymerization initiators, acylphosphine oxide-based polymerization initiators are preferred because they have sufficient curability (polymerization initiation) even when a UV-LED light source is used to reduce damage to the substrate. The above intramolecular bond cleavage type radical polymerization initiators may be used alone or in combination of two or more.

[0110] Examples of the intramolecular hydrogen abstraction type radical polymerization initiator include benzophenone-based initiators including benzophenone, methyl o-benzoylbenzoate, 4-phenylbenzophenone, 4,4'-dichlorobenzophenone, hydroxybenzophenone, 4-benzoyl-4'-methyl-diphenyl sulfide, acrylated benzophenone, 3,3',4,4'-tetra(tert-butylperoxycarbonyl)benzophenone, and 3,3'-dimethyl-4-methoxybenzophenone; thioxanthone-based initiators including 2-isopropylthioxanthone, 2,4-dimethylthioxanthone, 2,4-diethylthioxanthone, and 2,4-dichlorothioxanthone; aminobenzophenone-based initiators including Michler's ketone, 4,4'-diethylaminobenzophenone, and the like; 10-butyl-2-chloroacridone, 2-ethylanthraquinone, 9,10-phenanthrenequinone, and camphorquinone. The intramolecular hydrogen abstraction type radical polymerization initiator may be used alone or in combination of two or more.

[0111] The content of the polymerization initiator may be within a range that allows the active radiation curable composition to be sufficiently cured, and may be, for example, 0.01% by mass to 10% by mass relative to the total mass of the active radiation curable composition.

[0112] 1-5. Other ingredients

[0113] The active radiation curable composition may contain other components as long as the above-mentioned effects can be sufficiently obtained.

[0114] Examples of other components include (meth)acrylate oligomers, colorants, plasticizers, tackifiers, coupling agents such as silane coupling agents, antioxidants, polymerization inhibitors, surfactants, photosensitizers, polysaccharides, mildew inhibitors, rust inhibitors, ultraviolet absorbers, etc. The above-mentioned other components may be included in the above-mentioned composition alone or in combination of two or more.

[0115] Examples of the (meth)acrylate oligomer include epoxy (meth)acrylate oligomers, aliphatic urethane (meth)acrylate oligomers, aromatic urethane (meth)acrylate oligomers, polyoxyalkylene urethane (meth)acrylate oligomers, polyester (meth)acrylate oligomers, and linear (meth)acrylate oligomers.

[0116] From the viewpoint of further improving the flexibility of the cured film, the (meth)acrylate oligomer is preferably an oligomer having a (meth)acryloyl group less than two functional groups. In addition, from the viewpoint of further improving the ejection property from the inkjet head, the weight average molecular weight (Mw) of the (meth)acrylate oligomer is preferably 50,000 or less. Among them, from the viewpoint of appropriately imparting polarity to the cured film and further improving the adhesiveness and adhesiveness maintenance of the cured film, polyoxyalkylene carbamate (meth)acrylate oligomers are preferred.

[0117] Examples of the colorant include pigments including various organic pigments and inorganic pigments such as carbon black, and dyes.

[0118] The content of the colorant can be set according to the characteristics required by the cured film. Specifically, when it is desired to give a predetermined color tone to the cured film, the content of the colorant can be 0.1% by mass to 20.0% by mass, preferably 0.4% by mass to 10.0% by mass, relative to the total mass of the active ray curable composition. On the other hand, when it is desired to improve the permeability of the cured film, the content of the colorant is preferably 1% by mass or less, more preferably 0.1% by mass or less, relative to the total mass of the active ray curable composition.

[0119] 1-6.Physical properties

[0120] The viscosity of the active radiation curable composition at 25°C is 10 mPa·s to 200 mPa·s. If the viscosity at 25°C is 10 mPa·s or more, leakage from the inkjet head during standby can be suppressed. If the viscosity at 25°C is 200 mPa·s or less, ejection properties from the inkjet head can be ensured.

[0121] In the present specification, the viscosity of the active radiation curable composition is a value measured using a rheometer (Physica MCR301, manufactured by Anton Paar) under the condition of a shear rate of 1000 (1 / s).

[0122] 1-7. Application

[0123] The above-mentioned active radiation curable composition can be used as a so-called inkjet ink that can be ejected from an inkjet head to form a cured film in various applications using a cured film formed by an inkjet method.

[0124] In particular, the above-mentioned active ray-curable composition has high adhesiveness of the cured film and can also fully improve transparency, so it is suitable for forming a transparent layer of an image display device, especially a transparent layer for bonding various components of the image display device. Examples of the above-mentioned transparent layer include: a transparent layer for bonding a transparent electrode formed on a substrate to a glass or resin transparent protective layer, a transparent layer for bonding various panels such as a liquid crystal display panel, an organic EL display panel, and a touch panel to a transparent protective layer, a transparent layer for bonding a display panel such as a liquid crystal display panel and an organic EL display panel to a touch panel, and a transparent layer for bonding other components.

[0125] 2. Method for forming a cured film

[0126] The above-mentioned active radiation curable composition can be used to form a cured film.

[0127] In this case, the above-mentioned cured film can be obtained by applying an active radiation curable composition to the substrate or one of the members to be bonded, and curing the applied active radiation curable composition by irradiating the substrate with active radiation.

[0128] The imparting method of the active radiation curable composition is not particularly limited, and known methods such as spraying, dipping, screen printing, gravure printing, offset printing, and inkjet can be used. The above-mentioned imparting method can be used alone or in combination of two or more. Among them, from the viewpoint of forming a fine cured film with good precision, forming a high-precision pattern (image, etc.), or also imparting to a curved portion, the inkjet method is preferred.

[0129] The active ray curable composition can be applied to various substrates, or applied to one of the components to be bonded when two components are bonded. The material of the applied substrate or component is not particularly limited, and can be inorganic materials such as glass, metal, and ceramics, or organic materials such as resin films. The active ray curable composition can be well bonded regardless of the types of these materials.

[0130] At this time, the actinic radiation-curable composition provided above may be temporarily cured by irradiating the composition with actinic radiation to an extent that does not completely cure.

[0131] When forming a transparent layer for bonding two different members, another member is bonded onto the applied (or temporarily cured) active radiation curable composition. At this time, at least one of the two bonded members is a member that transmits active radiation.

[0132] Examples of components that transmit active radiation include components formed of materials such as glass, (meth) acrylic resin, polyethylene terephthalate resin, polyethylene naphthalate resin, polycarbonate resin, polyimide resin, and cycloolefin polymer. Transparent functional components such as transparent electrodes may also be formed on components formed of these materials.

[0133] Examples of the member that does not transmit active rays include a member formed with a liquid crystal display panel, an organic EL display panel, a protective panel, a touch panel, an organic EL element, a color filter, and the like.

[0134] After lamination, pressure may be appropriately applied in order to make these members adhere closely together or to make the thickness of the active radiation curable composition uniform.

[0135] Then, the active ray curable composition is irradiated with active rays to cure (or mainly cure), thereby obtaining a cured film. The active rays may be any active rays such as electron rays, ultraviolet rays, α rays, γ rays, and X rays, but ultraviolet rays are more preferred from the viewpoint of suppressing damage to other parts. In addition, from the viewpoint of suppressing damage to other parts by radiant heat, ultraviolet rays using a light emitting diode (UV-LED) that emits ultraviolet rays as a light source are more preferred.

[0136] The cured film formed from the active radiation curable composition has high adhesiveness and maintains good adhesiveness even in a high temperature and high humidity environment or a low temperature environment. Therefore, when used to bond two parts, the parts are not easily separated, especially when used for a long time.

[0137] Furthermore, the adhesiveness of the cured film is not easily reduced even when the cured film is repeatedly bent, so that even when the cured film is used in a flexible display or the like, the components are not easily detached, especially when the cured film is used for a long time.

[0138] Therefore, a device including the cured film, for example, an image display device including the cured film can be used for a long period of time.

[0139] 3. Cured film manufacturing device

[0140] Figure 1A to Figure 1C It is a schematic diagram which shows the exemplary structure of the manufacturing apparatus of the cured film for implementing the manufacturing method of the said cured film.

[0141] Figure 1A to Figure 1C The cured film manufacturing apparatus 100 shown includes an applying unit 120 for applying the above-mentioned active ray curable composition to the surface of a member 110 , and an irradiating unit 130 for irradiating the surface of the member 110 to which the active ray curable composition is applied with active rays.

[0142] In this embodiment, the imparting unit 120 imparts the active ray curable composition by inkjet method. The imparting unit 120 ejects the active ray curable composition from the nozzle 121, and imparts the active ray curable composition 122 ( Figure 1A ).

[0143] Then, the laminating unit 140 may be used to apply another member 150 to the surface of the applied active ray curable composition 122, and the one member 110 and the other member 150 may be laminated. In this embodiment, the laminating unit 140 delivers the other member 150 as a transparent film through the delivery roller 142 and applies it to the surface of the active ray curable composition. Then, the pressure roller 144 applies pressure to make the one member 110 and the other member 150 closely attached ( Figure 1B ).

[0144] In addition, when the one member 110 is a member that transmits active rays and the other member 150 is a member that does not transmit active rays, the manufacturing apparatus 100 may include a reversing unit that reverses them.

[0145] The irradiation unit 130 irradiates the surface of one component 110 to which the active ray curable composition 122 is applied with active rays. Thus, the irradiation unit 130 cures the active ray curable composition 122 applied to the surface of one component 110 to form a cured film 124. In this embodiment, the irradiation unit 130 irradiates the active ray that has passed through the other component 150 with the active ray curable composition 122 ( Figure 1C ).

[0146] It should be noted that in the above description, although the active radiation curable composition is imparted to the surface of a component 110 by an inkjet method, the method for imparting the active radiation curable composition is not particularly limited, and known methods such as spraying, dipping, screen printing, gravure printing, and offset printing can be used.

[0147] Example

[0148] Hereinafter, the present invention will be described in more detail, but the following description does not limit the present invention.

[0149] 1. Preparation of Materials

[0150] 1-1. Ingredients (A)

[0151] Methyl ethyl ketone (MEK) was added as a solvent to a three-necked flask, and the temperature was raised to 80°C while blowing nitrogen. A mixed solution of 83 parts of 2-ethylhexyl acrylate (2EHA) and 17 parts of 2-hydroxyethyl acrylate (2HEA) and 0.50 parts of azobisisobutyronitrile as a polymerization initiator was added dropwise over 2 hours. After the addition, the mixture was kept warm for 1 hour, and a solution obtained by dissolving 0.1 parts of azobisisobutyronitrile in MEK was added dropwise over 1 hour. Then, after keeping warm for about 1 hour, the reaction solution was diluted with MEK.

[0152] The acrylic polymer solution was added to a separable flask equipped with a stirrer, a thermometer, an air blowing tube, and a vacuum pump, and stirring and heating were started while bubbling air. The temperature was gradually raised to 80°C while reducing the pressure, and the pressure was continued while maintaining the temperature at 80°C to obtain an acrylic polymer.

[0153] HLC-8220GPC (manufactured by Tosoh Corporation) was used to connect TSG gel SuperMultiporeHZ 4000 (manufactured by Tosoh Corporation), TSG gel SuperMultiporeHZ 3000 (manufactured by Tosoh Corporation) and TSG gel SuperMultiporeHZ 2500 (manufactured by Tosoh Corporation) chromatographic columns to measure the weight average molecular weight (Mw) of (meth)acrylic polymer 1. Tetrahydrofuran (THF) was used as a solvent, the column temperature was set to 40°C, and the polystyrene-equivalent weight molecular weight was determined by detection using an RI (Refractive Index: differential refractive index) detector. The measured weight average molecular weight (Mw) of (meth)acrylic polymer 1 was 60,000.

[0154] With reference to JIS K0070, a potentiometric titrator (AT-500N, manufactured by Kyoto Electronics Co., Ltd.) and a glass electrode (C-173, manufactured by Kyoto Electronics Co., Ltd.) were used to measure the hydroxyl value of (meth)acrylic polymer 1 using an alcohol solution with a KOH concentration of 0.5 mol / L as a titrant. The sample was weighed in a 200 mL conical flask, 5 mL of an acetylation reagent was added, and the mixture was reacted in an oil bath at 100°C ± 5°C for 1 hour. After cooling, 1 mL of water was added, and the mixture was reacted in an oil bath at 100°C ± 5°C for 10 minutes. After cooling, 5 mL of ethanol was used to rinse the mixture, and 140 mL of pyridine was added to dilute the mixture. The titration was performed using a potentiometric titrator, and the inflection point obtained was taken as the end point. A blank test was also performed using the same method, and the hydroxyl value was calculated using the following formula.

[0155] Hydroxyl value (mgKOH / g) = (V0-V1) × N × 56.11 × f / S + acid value

[0156] S: weight of sample (g)

[0157] V0: The amount of titrant required for the blank test (mL)

[0158] V1: The amount of titrant required for this test (mL)

[0159] N: concentration of titration solution (0.5 mol / L)

[0160] f: Factor of the titrant (1.001)

[0161] It should be noted that the acid value in the above calculation formula is a value measured with reference to JIS K 0070, using a potentiometric titrator (manufactured by Kyoto Electronics Co., Ltd., AT-500N), a glass electrode (manufactured by Kyoto Electronics Co., Ltd., C-173), and an alcohol solution with a KOH concentration of 0.1 mol / L as a titrant. In a 100 mL conical flask, add the sample and 80 mL of a mixed solution (toluene: methanol = 4:1) (volume ratio) to dissolve the sample. Titrate using a potentiometric titrator, and take the inflection point obtained as the end point. A blank test is also performed using the same method, and the acid value is calculated by the following formula.

[0162] Acid value (mgKOH / g) = (V1-V0) × N × 56.11 × f / S

[0163] S: weight of sample (g)

[0164] V0: The amount of titrant required for the blank test (mL)

[0165] V1: The amount of titrant required for this test (mL)

[0166] N: concentration of titration solution (0.1 mol / L)

[0167] f: Factor of the titrant (1.001)

[0168] The hydroxyl value of the (meth)acrylic polymer 1 measured by the above method was 80 mgKOH / g.

[0169] The monomer (2EHA and 2HEA) feed ratio and reaction time were changed to obtain solutions of (meth)acrylic polymers 2 to 10. The weight average molecular weight (Mw) and hydroxyl value of these (meth)acrylic polymers were measured in the same manner as for (meth)acrylic polymer 1.

[0170] Tables 1 and 2 show the weight average molecular weight (Mw) and hydroxyl values ​​of (meth)acrylic polymers 1 to 10.

[0171] [Table 1]

[0172] (Meth) acrylic acid polymer number 1 2 3 4 5 Weight average molecular weight (Mw) 60,000 60,000 60,000 60,000 60,000 Hydroxyl value (mgKOH / g) 80 30 115 0 150

[0173] [Table 2]

[0174] (Meth) acrylic acid polymer number 6 7 8 9 Weight average molecular weight (Mw) 5,000 10,000 120,000 200,000 Hydroxyl value (mgKOH / g) 80 80 80 80

[0175] 1-2. Component (B)

[0176] As the (meth)acrylate having a hydroxyl group, hydroxybutyl acrylate (HBA) was used.

[0177] 1-3. Ingredient (C)

[0178] As the (meth)acrylate having no hydroxyl group, isostearyl acrylate (ISTA) and isobornyl acrylate (IBXA) were used. In addition, as the polyfunctional (meth)acrylate, trimethylolpropane triacrylate (TMPTA) was used.

[0179] 1-4. Ingredient (D)

[0180] As the photopolymerization initiator, bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide (manufactured by IGM Resin, Omnirad 819, cleavage type, acylphosphine oxide series), methyl benzoylformate (manufactured by IGM Resin, Omnirad MBF, hydrogen abstraction type) and 2-hydroxy-2-methyl-1-phenylpropane (manufactured by Lambson, Speedcure 84, cleavage type) were used.

[0181] 2. Preparation of active radiation curable composition

[0182] The above materials were placed in a stainless steel beaker at the ratio shown in Table 1, and stirred for 1 hour while heating to 80° C. on a hot plate. Then, the mixture was filtered through a filter (PTFE membrane filter manufactured by ADVANTEC, pore size 3.00 μm) to obtain Ink 1 to Ink 16, all of which were active radiation curable compositions.

[0183] The compositions of Ink 1 to Ink 16 are shown in Tables 3 and 4. In addition, the units of the amounts described in Tables 3 and 4 are parts by mass.

[0184] [Table 3]

[0185]

[0186] [Table 4]

[0187]

[0188] 3. Evaluation

[0189] Ink 1 to Ink 16 were evaluated for viscosity, discharge stability from an inkjet head, high-temperature and high-humidity durability of a cured product, low-temperature durability of a cured product, and flexural durability of a cured product using the following methods and criteria.

[0190] 3-1. Viscosity

[0191] The viscosity of each ink at 25° C. was measured using a rheometer (Physica MCR301, manufactured by Anton Paar) at a shear rate of 1000 (1 / s).

[0192] 3-2. Ejection stability from inkjet head

[0193] An inkjet head (KM1024iLHE-30, manufactured by Konica Minolta, Inc.) was installed in an inkjet image forming apparatus (manufactured by Tritech Corporation), and the resolution was set to 360 dpi×360 dpi. Ink 1 to Ink 16 were continuously ejected while the ink in the flow path in the nozzle was heated to a temperature with a viscosity of 10 to 11 mPa·s.

[0194] At this time, the ejection speed from the single nozzle was set to 6 m / s, and the ejection speed was measured 10 times at 1-minute intervals after the start of continuous ejection for 1 minute.

[0195] In addition, the ejection speed was measured by the following method.

[0196] First, a CCD camera is set in a position to shoot in a direction parallel to the ejection surface in a space (flight space) on one side (base side) below the ejection surface of the nozzle so that the ejected and flying droplets can be shot from the lateral direction. In addition, a flash lamp is set at a position opposite to the CCD camera across the flight space to illuminate the flight space. The flying droplets are continuously shot by emitting light from the flash lamp and continuously shooting the flight space with the CCD camera.

[0197] At this time, the time from the output of the signal for driving the inkjet head to eject ink droplets from each nozzle (droplet ejection trigger) until the flash lamp is lit and the flight space is photographed by the CCD camera (delay time 1) is set to 100 μsec. In addition, the time from the delay time 1 to the flash lamp is lit and the flight space is photographed next time by the CCD camera (delay time 2) is set to 100 μsec.

[0198] Then, the position of the center of gravity of the ink droplet in the image is obtained based on the image captured during delay time 1, and the position of the center of gravity is determined based on the position on the orthogonal X-axis and Y-axis set in the image. The position of the center of gravity of the ink droplet in delay time 1 is set to (X1, Y1). The position of the center of gravity of the same ink droplet in the image is also obtained based on the image captured during delay time 2, and the position of the center of gravity is determined in the same manner. The position of the center of gravity of the ink droplet in delay time 2 is set to (X2, Y2).

[0199] Then, the ejection speed of the ink droplets is calculated by the following formula.

[0200]

[0201] Among the ejection speeds measured 10 times at one minute intervals, the maximum ejection speed was taken as the maximum speed, and the minimum ejection speed was taken as the minimum speed, and the speed fluctuation value was calculated by the following formula.

[0202]

[0203] Using the velocity fluctuation values ​​obtained above, the ejection stability of each ink from the inkjet head was evaluated according to the following criteria.

[0204] ◎ The speed fluctuation is less than 5%

[0205] ○ The speed fluctuation is greater than 5% and less than 30%

[0206] × The speed fluctuation is greater than 30%

[0207] ×× Ink is not ejected from the nozzle

[0208] 3-3. High temperature and high humidity durability of cured products

[0209] Using the inkjet image forming apparatus and inkjet head used in "3-2. Discharge stability from inkjet head", each ink was applied to a glass plate as a substrate so that the film thickness was 50 μm. An ultraviolet irradiation device (manufactured by Phoseon) was used at an intensity of 200 mW / cm 2 The applied ink is irradiated with ultraviolet light of wavelength 395nm. The accumulated light intensity is 1000mJ / cm 2 A transparent PET film (thickness 50 μm) was attached to the surface of the ink that was temporarily cured by the irradiation, and then irradiated with an intensity of 200 mW / cm 2 、Accumulated light quantity 1000mJ / cm 2 The ink was primarily cured by irradiation with ultraviolet light having a wavelength of 395 nm, thereby obtaining a test piece in which a cured film of each ink was sandwiched between a glass plate and a PET film (hereinafter also referred to as a "peeling test piece").

[0210] The peel test pieces obtained from each ink were placed on a tensile testing machine (TG-2kN, manufactured by Minebea Corporation) and subjected to a 180° peel test at a tensile speed of 60 mm / min. The average value of the stress when the PET film was peeled off by about 60 mm was taken as the peel force of the cured product of each ink (before storage).

[0211] The peel test pieces obtained from each ink were stored in a thermostatic chamber set at a temperature of 85°C and a relative humidity of 85%, and taken out after 500 hours. The cured product after storage was subjected to a 180° peel test under the same conditions, and the average stress when the PET film was peeled off by about 60 mm was taken as the peeling force of the cured product of each ink (after high temperature and high humidity storage).

[0212] The ratio of the fluctuation of the peel force (after high-temperature and high-humidity storage) to the peel force (before storage) was determined, and the high-temperature and high-humidity durability of the cured product of each ink was evaluated according to the following criteria.

[0213] ◎◎ The fluctuation ratio is less than 2.5%

[0214] ◎ The fluctuation ratio is greater than 2.5% and less than 5%

[0215] ○ The fluctuation ratio is greater than 5% and less than 30%

[0216] × The fluctuation ratio is greater than 30% and less than 50%

[0217] ×× The fluctuation ratio is greater than 50%

[0218] 3-4. Low temperature durability of cured products

[0219] The peel test pieces of each ink used in "3-3. High-temperature and high-humidity durability of cured product" were stored in a thermostatic chamber set at 0°C and taken out after 500 hours. The peel test pieces after storage were subjected to a 180° peel test under the same conditions, and the average stress when the PET film was peeled off by about 60 mm was taken as the peel strength of the cured product of each ink (after low-temperature storage).

[0220] The ratio of the fluctuation of the peel force (after low-temperature storage) to the peel force (before storage) was determined, and the high-temperature and high-humidity durability of the cured product of each ink was evaluated according to the following criteria.

[0221] ◎ The fluctuation ratio is less than 5%

[0222] ○ The fluctuation ratio is greater than 5% and less than 30%

[0223] × The fluctuation ratio is greater than 30% or less

[0224] 3-5. Bending durability of cured products

[0225] Using the inkjet image forming apparatus and inkjet head used in "3-2. Discharge stability from inkjet head", each ink was applied to a PET film (film thickness 50 μm) as a substrate to a film thickness of 30 μm. An ultraviolet irradiation device (manufactured by Phoseon) was used at an intensity of 200 mW / cm 2 The applied ink is irradiated with ultraviolet light of wavelength 395nm. The accumulated light intensity is 1000mJ / cm 2 A transparent PET film (thickness 50 μm) was attached to the surface of the ink that was temporarily cured by the irradiation, and then irradiated with an intensity of 200 mW / cm 2 、Accumulated light quantity 1000mJ / cm 2 The ink was primarily cured by irradiation with ultraviolet light having a wavelength of 395 nm, to obtain a test piece in which a cured film of each ink was sandwiched between two PET films (hereinafter also referred to as a "bending test piece").

[0226] The folding test pieces obtained from each ink were placed on a folding tester and subjected to a folding test at R = 2 mm for 100,000 times. The cured film after the test was visually observed, and the folding durability of the cured product of each ink was evaluated based on changes such as white turbidity compared to the cured film before the test according to the following criteria.

[0227] ◎ No changes such as white turbidity were observed

[0228] ○ Vaguely see white turbidity and other changes

[0229] △ Slightly visible changes such as white turbidity

[0230] × Clearly see changes such as white turbidity

[0231] Tables 5 and 6 show the weight average molecular weight (Mw) and hydroxyl value of the component (A) added to each ink and the evaluation results of each ink.

[0232] [Table 5]

[0233]

[0234] [Table 6]

[0235]

[0236] Tables 5 and 6 show that the active radiation curable composition containing components (A) to (D) can provide a cured film having good discharge stability and good durability in a high temperature and high humidity environment, durability at low temperatures, and durability against bending.

[0237] This application claims the benefit of priority of Japanese Patent Application No. 2022-085423 filed on May 25, 2022. The entire contents of the original specification, claims, and drawings of that application are incorporated herein by reference.

[0238] Industrial Applicability

[0239] According to the present invention, a cured film can be obtained which can form a high-definition pattern by an inkjet method and has high durability in a high-temperature and high-humidity environment and a low-temperature environment, and high durability against bending. The present invention improves the durability of cured films used in various applications, especially image display devices, and is expected to contribute to the further popularization of cured films formed by an inkjet method.

[0240] Explanation of symbols

[0241] 100 Cured film manufacturing device

[0242] 110 A component

[0243] 120 Endowment Department

[0244] 122 Active ray curable composition

[0245] 124 cured film

[0246] 130 Irradiation Department

[0247] 140 Lamination Department

[0248] 142 Feeding roller

[0249] 144 Pressure roller

[0250] 150 Another part

Claims

1. An active radiation curable composition comprising: Component (A): a (meth)acrylic acid polymer having a weight average molecular weight of 10,000 to 150,000 and a hydroxyl value of 30 mgKOH / g or more, Component (B): (meth)acrylate having a hydroxyl group, Component (C): (meth)acrylate having no hydroxyl group, and Component (D): photopolymerization initiator, And the viscosity at 25°C is 10 mPa·s to 200 mPa·s.

2. The active radiation curable composition according to claim 1, wherein The component (C) contains a (meth)acrylate having an alicyclic structure.

3. The active radiation curable composition according to claim 1 or 2, wherein The component (C) contains a (meth)acrylate having no alicyclic structure.

4. The active radiation curable composition according to any one of claims 1 to 3, wherein The component (B) or the component (C) contains a multifunctional (meth)acrylate.

5. The active radiation curable composition according to any one of claims 1 to 4, wherein The component (A) is a (meth)acrylic acid polymer having a weight average molecular weight of 20,000 to 100,000.

6. The active radiation curable composition according to any one of claims 1 to 5, wherein The component (D) is an intramolecular bond cleavage type photopolymerization initiator.

7. The active radiation curable composition according to any one of claims 1 to 6, wherein The component (D) is an acylphosphine oxide-based photopolymerization initiator.

8. The active radiation curable composition according to any one of claims 1 to 7, wherein The component (B) is contained in an amount of 25% by mass or more based on the total mass of the active radiation curable composition.

9. The active radiation curable composition according to any one of claims 1 to 8, wherein The component (A) is a (meth)acrylic acid polymer having a hydroxyl value of 30 mgKOH / g to 120 mgKOH / g. 10 . The active radiation curable composition according to claim 1 , which is an inkjet ink. 11 . The active radiation curable composition according to claim 1 , which is used for forming a transparent layer of an image display device.

12. A method for producing a cured film, comprising: A step of providing the active radiation curable composition according to any one of claims 1 to 11, and A step of irradiating the provided active ray-curable composition with active rays. 13 . A cured film obtained by curing the active radiation-curable composition according to claim 1 . The cured film according to claim 13 , which is a transparent layer of an image display device. 15 . An image display device comprising the cured film according to claim 13 or 14 .

16. A device for manufacturing a cured film, comprising: an applying unit that applies the active radiation curable composition according to any one of claims 1 to 11 to a substrate; and The irradiation unit irradiates the provided active ray-curable composition with active rays.